“Now in respect it is in the fields, it pleaseth me well; but in respect it is not in the court, it is tedious”: Theatre between Court and Country - Seress, Ákos (FOCUS: Papers in English Literary and Cultural Studies, 2014)
According to Hungarian literary scholars László Kéry and Marcell Benedek, Adam from Shakespeare’s As You Like It and Bence from János Arany’s Toldi are much alike (Benedek 200, Kéry 184). Both old servants are brave, honest, and faithful to their masters. Be that as it may, a more conspicuous resemblance can be found, and that is the similarity between the main protagonists: Orlando and Toldi. Shakespeare’s character has two siblings, but his older brother treats him just as poorly as does György Toldi his brother Miklós. Despite his noble birth, he keeps him as a servant, denying him the possibility of learning. Also, as it becomes clear in the first act, Orlando’s physical power is outstanding since he manages to beat Charles, the wrestling champion, without any real effort. This scene can easily conjure up Toldi’s fight with the Czech champion, where the hero kills his enemy due to his extreme strength. Moreover, the Hungarian hero manages to survive the attacks of various beasts, as does Orlando, who saves his brother from a lion. The question this paper intends to explore can be formulated as follows: can we say that Orlando is also a representative character of the higher morals of the country? Is he braver, smarter, etc. than his brother because he was raised outside of the court? Did Shakespeare in As You Like It write the apology of the country and a criticism of the Palace? In the following I am about to investigate these issues.